Low ceruloplasmin in a patient with Niemann-Pick Type C disease - Connemann, Bernhard J.; Runz, Heiko (Journal of clinical neuroscience, 2012)
We present a 28-year-old woman with a diagnosis of Niemann-Pick type C disease which was initially diagnosed as Wilson disease due to low serum ceruloplasmin and elevated free copper. This report supports the hypothesis that NPC1 could play a role in copper metabolism.